Users' perception towards selected recreational forest landscape maintenance in Selangor Darul Ehsan, Malaysia - Hussein, Mohd Kher (Universiti Putra Malaysia Press, 2014)
Landscape maintenance plays an important role in ensuring the landscape sustainability of recreational forest. Proper landscape maintenance can enhance park's quality as well as increase user experience in the park. As new recreational forests are developed, the need for good landscape maintenance and management geared towards sustainability is crucial. The goal of this study is to understand users' perception towards recreational forest landscape maintenance and management. The objective of this study is to analyze users' perception towards landscape maintenance of recreational forests in relation to their existing management programs, and to discuss implications of maintenance and management of recreational forest towards sustainability. The study is conducted at three selected recreational forests in Selangor, namely Sungai Tekala Recreational Forest, Sungai Chongkak Recreational Forest and Templer Recreational Forest. A total of 533 respondents participated in this study. Results indicate that the present landscape maintenance standards of these sites are low reflecting weaknesses in the management system. Therefore, the management team of these recreational forests must improve their landscape maintenance and management approaches for sustainability including improving users' convenience, safety and experience.